Financial incentives for physical activity in adults: systematic review and meta-analysis. Issue 21 (15th May 2019) - Mitchell, Marc S; Orstad, Stephanie L; Biswas, Aviroop; Oh, Paul I; Jay, Melanie; Pakosh, Maureen T; Faulkner, Guy
Abstract : Objective: The use of financial incentives to promote physical activity (PA) has grown in popularity due in part to technological advances that make it easier to track and reward PA. The purpose of this study was to update the evidence on the effects of incentives on PA in adults. Data sources: Medline, PubMed, Embase, PsychINFO, CCTR, CINAHL and COCH. Eligibility criteria: Randomised controlled trials (RCT) published between 2012 and May 2018 examining the impact of incentives on PA. Design: A simple count of studies with positive and null effects ('vote counting') was conducted. Random-effects meta-analyses were also undertaken for studies reporting steps per day for intervention and post-intervention periods. Results: 23 studies involving 6074 participants were included (64.42% female, mean age = 41.20 years). 20 out of 22 studies reported positive intervention effects and four out of 18 reported post-intervention (after incentives withdrawn) benefits. Among the 12 of 23 studies included in the meta-analysis, incentives were associated with increased mean daily step counts during the intervention period (pooled mean difference (MD), 607.1; 95% CI: 422.1 to 792.1). Among the nine of 12 studies with post-intervention daily step count data incentives were associated with increased mean daily step counts (pooled MD, 513.8; 95% CI:312.7 to 714.9). Conclusion: Demonstrating rising interest in financial incentives, 23 RCTs were identified. Modest incentives ($1.40 US/day) increased PA for interventions of short and long durations and after incentives were removed, though post-intervention 'vote counting' and pooled results did not align. Nonetheless, and contrary to what has been previously reported, these findings suggest a short-term incentive 'dose' may promote sustained PA.